Kinematics of Convergence and Deformation in Luzon Island and Adjacent Sea Areas： 2-D Finite-Element Simulation - 刘再峰 詹文欢 姚衍桃 詹美珍 张殿广 (Journal of earth science (Wuhan, China), 2009)
The Luzon Island is a volcanic arc sandwiched by the eastward subducting South China Sea and the northwestward subducting Philippine Sea plate. Through experiments of plane-stress, elastic, and 2-dimensional finite-element modeling, we evaluated the relationship between plate kinematics and present-day deformation of Luzon Island and adjacent sea areas. The concept of coupling rate was applied to define the boundary velocities along the subduction zones. The distribution of velocity fields calculated in our models was compared with the velocity field revealed by recent geodetic （GPS） observations. The best model was obtained that accounts for the observed velocity field within the limits of acceptable mechanical parameters and reasonable boundary conditions. Sensitivity of the selection of parameters and boundary conditions were evaluated. The model is sensitive to the direction of convergence between the South China Sea and the Philippine Sea plates, and to different coupling rates in the Manila trench, Philippine trench and eastern Luzon trough. We suggest that a change of ±15° of the direction of motion of the Philippine Sea plate can induce important changes in the distribution of the computed displacement trajectories, and the movement of the Philippine Sea plate toward azimuth 330° best explains the velocity pattern observed in Luzon Island. In addition, through sensitivity analysis we conclude that the coupling rate in the Manila trench is much smaller compared with the rates in the eastern Luzon trough and the Philippine trench. This indicates that a significant part of momentum of the Philippine Sea plate motion has been absorbed by the Manila trench; whereas, a part of the momentum has been transmitted into Luzon Island through the eastern Luzon trough and the Philippine trench.